Assessment of the quality of life of pediatric patients with multiple sclerosis - Nailya F. Akhmetgaleeva; Taras O. Simaniv; Klara Z. Bakhtiyarova (Consilium Medicum)
Background. Multiple sclerosis (MS) is a chronic Demyelinating disease, the onset of MS occurs in childhood in 5% of cases. MS has a great impact on the quality of life (QoL) of children, especially during periods of exacerbation of the disease.